Influence of Sonographic Fetal Weight Estimation Inaccuracies in Macrosomia on Perinatal Outcome - Pretscher, Jutta; Kehl, Sven; Stelzl, Patrick; Stumpfe, Florian Matthias; Mayr, Andreas; Schmid, Matthias; Staerk, Christian; Schild, Ralf; Beckmann, Matthias W.; Faschingbauer, Florian (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Objective To evaluate the influence of inaccurate sonographic fetal weight estimation in macrosomia on the mode of delivery and neonatal outcome (NO).Methods In 14 633 pregnancies between 2002 and 2016, this retrospective study evaluated the association between sonographic fetal weight estimation, true birth weight (BW), mode of delivery (primary cesarean section [pCS], secondary cesarean section, vaginal delivery, and operative vaginal delivery rates) and NO parameters (5-min Apgar < 7, pH < 7.1, neonatal intensive care unit [NICU] admission, shoulder dystocia). Singleton pregnancies > 37 + 0 weeks with ultrasound-estimated fetal weight (EFW) within 7 days before delivery were included. The study population was divided into four groups: Group 1 (false-negative): EFW < 4000 g/BW ≥ 4000 g; Group 2 (true-positive): EFW ≥ 4000 g/BW ≥ 4000 g; Group 3 (false-positive): EFW ≥ 4000 g/BW < 4000 g; and Group 4 (true-negative): EFW < 4000 g/BW < 4000 g.Results As expected, the highest secondary cesarean section (sCS) rate was found in Group 2 (true-positive) (30.62 %), compared with only 17.68 % in Group 4 (true-negative). The sCS rate in the false-positive Group 3 was significantly higher (28.48 %) in comparison with the false-negative Group 1 (21.22 %; OR 1.48; 95 % CI, 1.16 to 1.89; P = 0.002). In comparison with the true-negative Group 4, univariate analyses showed significantly higher rates for sCS in all other groups: odds ratio (OR) 2.06 for Group 2 (95 % CI, 1.74 to 2.42; P < 0.001), 1.85 for Group 3 (95 % CI, 1.54 to 2.22, P < 0.001), and 1.25 for Group 1 (95 % CI, 1.05 to 1.49; P < 0.01). No significant differences were found for NO between Groups 1 and 3 for the parameters 5-min Apgar < 7 (P = 0.75), pH < 7.1 (P = 0.28), or NICU admission (P = 0.54). However, there was a significantly higher chance for shoulder dystocia in Group 1 compared with Group 3 (OR 4.58; 95 % CI, 1.34 to 24.30; P = 0.008).Conclusion Sonographic EFW inaccuracies in fetal macrosomia appear to have a greater impact on the mode of delivery than birth weight itself. Underestimation of fetal weight may be associated with a higher probability of shoulder dystocia.
Keywords: cesarean section rate; fetal weight estimation; fetal macrosomia; perinatal outcome; sonography